Use of radioiodine‐131 scan to measure influence of surgical discipline, practice, and volume on residual thyroid tissue after total thyroidectomy for differentiated thyroid carcinoma. Issue 10 (13th May 2018) - Song, Jin Soo A.; Moolman, Nico; Burrell, Steven; Rajaraman, Murali; Bullock, Martin Joseph; Trites, Jonathan; Taylor, S. Mark; Rigby, Matthew H.; Hart, Robert D.
Abstract: Background: Our study's purpose is to determine the influence of surgical discipline, surgeon site, and volume on remnant thyroid tissue visualized on radioactive iodine‐131 (I‐131) scans after total thyroidectomy and I‐131 ablation in patients with well‐differentiated thyroid carcinomas. Methods: We retrospectively reviewed all cases of patients who received I‐131 therapeutic ablation and postablation radioactive I‐131 scans at our center after thyroidectomy to calculate the fraction of administered dose multiplied by 1000 (UDR1000). Results: The remnant thyroid tissue (ie, the UDR1000), between academic and community surgeons was 0.471 (±0.705) and 1.190 (±2.487), respectively ( P = .001). The UDR1000 between otolaryngology‐head and neck surgery and general surgery was 0.654 (±1.575) and 1.043 (±1.625), respectively ( P = .159). The UDR1000 partitioned by patient frequencies of <10, 10 to 19, and ≥20 patients yielded 1.255 (±2.554), 0.926 (±2.084), and 0.467 (±0.721), respectively ( P = .003). Conclusion: Our study found statistically significant differences in residual thyroid tissue visualized on radioactive I‐131 scans based on surgeon parameters.